2017
DOI: 10.1108/jsit-06-2016-0038
|View full text |Cite
|
Sign up to set email alerts
|

Online information seeking behaviour among people living with HIV in selected public hospitals of Tanzania

Abstract: Purpose This paper aims to determine factors that influence people living with HIV (PLHIV) to engage in internet-based HIV information seeking behaviour in selected Tanzanian public regional hospitals. Design/methodology/approach The authors conducted a questionnaire-based survey to 221 PLHIV in two regional public hospitals in Mwanza and Dar es Salaam, Tanzania. They assessed the validity and reliability of the measurement model by using exploratory factor analysis and also used hierarchical regressions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 38 publications
6
20
0
Order By: Relevance
“…However, there is no any mobile application platform for dissemination of HIV/AIDS healthcare information in Tanzania to date. [6] made a call for online dissemination of HIV/AIDS healthcare information since there is a considerably people's high effort to try to access to internet-based HIV information, HIV/AIDS clinical tips and recommendations.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is no any mobile application platform for dissemination of HIV/AIDS healthcare information in Tanzania to date. [6] made a call for online dissemination of HIV/AIDS healthcare information since there is a considerably people's high effort to try to access to internet-based HIV information, HIV/AIDS clinical tips and recommendations.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, this study finds that there is a massive increase in number of people who seek the HIV/AIDS related information from the internet sources. [6] stipulated that there is a considerably people's high effort to access to internet-based HIV information. Some previous studies indicated that Internet technologies improvements have vastly increased access of healthcare information [36][37][38][39].…”
Section: Hiv/aids Practitioners' Readiness Towards Online Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…There is a need of extending the use of the mobile Web- [10] recommended that the HIV/AIDS public care providers, and the HIV/AIDS Care and Treatment Centers (CTCs) to use the electronic media to provide access to relevant and formal HIV/AIDS healthcare information. Particularly, healthcare information delivery for HIV care and treatment should make use of internet and mobile phones to reach many people for broader coverage and impact.…”
Section: Introductionmentioning
confidence: 99%
“…This fear is due to the lack of a secured platform for accessing the HIV/AIDS healthcare information services. [10] recommended that the HIV/AIDS public healthcare providers, and the HIV/AIDS CTCs to use the electronic platform to provide a confidential access to relevant and formal HIV/AIDS healthcare information. Despite the need for the m-health platform for enhancement of HIV/AIDS healthcare delivery, there is no any m-health platform for dissemination of HIV/AIDS healthcare information in Tanzania to date.…”
Section: Introductionmentioning
confidence: 99%